Digital pre-distortion for 5G transmission over high-capacity optical fronthaul fiber links - Fernandes, Marco André Tavares (2020)
The new generations of radio communications bring many challenges for the fronthaul transport. While demanding larger capacity than previous generations, low cost, low complexity, low power consumption and low latency are required characteristics. This thesis explores the possibility of using analog radio-over-fiber (RoF) fronthaul transmission in a centralized-radio access network. We propose and study the use of low-cost transceivers based on commercially available small form-factor pluggable (SFP) transceivers adapted to transport analog signals. The transceiver performance is experimentally characterized both with 4G LTE and 5G signals. The studies of this thesis include the impact of the carrier frequency, transmitted RF power, received optical power as well as distance of the fiber link. Additionally, the benefits of a low-complexity memory polynomial-based nonlinear compensation are evaluated. This nonlinear compensation enables high-performance 5G operation yielding an EVM < 3.5% in frequency region 1 (FR1) with 100 MHz bandwidth, which is below the limits speci ed by 3GPP for 256QAM transmission . In addition it also reduces the EVM from 5.7% to 5.4% when transmitting over 20 km a FR2 400 MHz 5G signal at an intermediate carrier frequency of 3.5 GHz.